2019
DOI: 10.15282/jgi.3.1.2019.5422
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Quality of Chief Integrity Officer, Ethical Climate on the Level of Ethics and Integrity in the Malaysian Federal

Abstract: The purpose of this quantitative study is to examine the relationship between the level of ethics and integrity with Quality of Chief Integrity Officer (independence, competence, work performance) and ethical climate in the Malaysian public-sector organizations. Out of 128 questionnaires that were emailed to CIOs in the Federal level, 83 questionnaires were received and usable. The results of this study showed that the Quality of CIO (competence, work performance) and ethical climate is significantly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…As regards staff nurses highly perceived professional values, ethical behavior and ethical climate. This was in the same line with Sajari, Haron & Ismail (2019); Abdullah, Sulong & Said (2019) and Barimani et al, (2019) who found that the respondent perceived ethical climate highly. The result was opposite to study done by Farsaraei et al, (2017) who reported that respondents perceived ethical climate negatively.…”
Section: Discussionsupporting
confidence: 85%
“…As regards staff nurses highly perceived professional values, ethical behavior and ethical climate. This was in the same line with Sajari, Haron & Ismail (2019); Abdullah, Sulong & Said (2019) and Barimani et al, (2019) who found that the respondent perceived ethical climate highly. The result was opposite to study done by Farsaraei et al, (2017) who reported that respondents perceived ethical climate negatively.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the public sector organisation's level of ethics and integrity score was at a moderate level with a score of 73.67%. This is in line with the study by Sajari, Haron, and Ismail (2017) and Zainal, Som, and Mohamed (2020). It can be seen from Table 5 that Dimension 1 -Vision and Goal showed an overall score of 79.47%.…”
Section: Analysis Of the Level Of Ethics And Integritysupporting
confidence: 90%
“…Many studies assess the level of ethics and integrity of public sector organisations and findings are compared to the present study. Sajari, Haron, & Ismail (2017) conducted a study on a public sector organisation. Questionnaires were distributed to the employees of the agency, and they were asked to rate on a scale of 1 to 5 their perceptions on a list of statements addressing the 12 dimensions.…”
Section: Previous Literaturementioning
confidence: 99%
“…The CIO and Integrity Units may also have had a mixed impact. A study by Sajari et al (2019, pp. 54-57, 60-65) reported favourably on their performance which nonetheless depended on the “ethical climate” in the organisation including the influence of top management.…”
Section: The Reasons For the Persistence Of Corruption In Malaysiamentioning
confidence: 99%